Astrocytes—The Ultimate Effectors of Long-Range Neuromodulatory Networks? - Pacholko, Anthony G.; Wotton, Caitlin A.; Bekar, Lane K. (Frontiers in Cellular Neuroscience, 2020)
It was long thought that astrocytes, given their lack of electrical signaling, were not involved in communication with neurons. However, we now know that one astrocyte on average maintains and regulates the extracellular neurotransmitter and potassium levels of more than 140,000 synapses, both excitatory and inhibitory, within their individual domains, and form a syncytium that can propagate calcium waves to affect distant cells via release of ‘gliotransmitters’ such as glutamate, ATP, or adenosine. Neuromodulators can affect signal-to-noise and frequency transmission within cortical circuits by effects on inhibition, allowing for the filtering of relevant versus irrelevant stimuli. Moreover, synchronized ‘resting’ and desynchronized ‘activated’ brain states are gated by short bursts of high-frequency neuromodulatory activity, highlighting the need for neuromodulation that is robust, rapid, and far-reaching. As many neuromodulators are released in a volume manner where degradation/uptake and the confines of the complex CNS limit diffusion distance, we ask the question – are astrocytes responsible for rapidly extending neuromodulator actions to every synapse? Neuromodulators are known to influence transitions between brain states, leading to control over plasticity, responses to salient stimuli, wakefulness, and sleep. These rapid and wide-spread state transitions demand that neuromodulators are able to simultaneously influence large and diverse regions in a manner that should be impossible given the limitations of simple diffusion. Intriguingly, astrocytes are ideally situated to amplify/extend neuromodulator effects over large populations of synapses given that each astrocyte can 1) ensheath a large number of synapses, 2) release gliotransmitters (glutamate/ATP/adenosine) known to affect inhibition, 3) regulate extracellular potassium that can affect excitability and excitation/inhibition balance, and 4) express receptors for all neuromodulators. In this review, we explore the hypothesis that astrocytes extend and amplify neuromodulatory influences on neuronal networks via alterations in calcium dynamics, the release of gliotransmitters, and potassium homeostasis. Given that neuromodulatory networks are at the core of our sleep-wake cycle and behavioral states, and determine how we interact with our environment, this review highlights the importance of basic astrocyte function in homeostasis, general cognition, and psychiatric disorders.